How Thailand's greater convergence created sustainable funding for emerging health priorities caused by globalization - Naowarut Charoenca; Nipapun Kungskulniti; Jeremiah Mock; Stephen Hamann; Prakit Vathesatogkit (Taylor & Francis Group, 2015)
Background: Global health is shifting gradually from a limited focus on individual communicable disease goals to the formulation of broader sustainable health development goals. A major impediment to this shift is that most low- and middle-income countries (LMICs) have not established adequate sustainable funding for health promotion and health infrastructure. Objective: In this article, we analyze how Thailand, a middle-income country, created a mechanism for sustainable funding for health. Design: We analyzed the progression of tobacco control and health promotion policies over the past three decades within the wider political-economic and sociocultural context. We constructed a parallel longitudinal analysis of statistical data on one emerging priority - road accidents - to determine whether policy shifts resulted in reduced injuries, hospitalizations and deaths. Results: In Thailand, the convergence of priorities among national interest groups for sustainable health development created an opportunity to use domestic tax policy and to create a semi-autonomous foundation (ThaiHealth) to address a range of pressing health priorities, including programs that substantially reduced road accidents. Conclusions: Thailand's strategic process to develop a domestic mechanism for sustainable funding for health may provide LMICs with a roadmap to address emerging health priorities, especially those caused by modernization and globalization.